Mechanically stable tuning fork sensor with high quality factor for the atomic force microscope. Issue 6 (17th September 2014) - Kim, Kwangyoon; Park, Jun‐Young; Kim, K.B.; Lee, Naesung; Seo, Yongho
Summary A quartz tuning fork was used instead of cantilever as a force sensor for the atomic force microscope. A tungsten tip was made by electrochemical etching from a wire of 50 µm diameter. In order to have mechanical stability of the tuning fork, it was attached on an alumina plate. The tungsten tip was attached on the inside end of a prong of a tuning fork. The phase shift was used as a feedback signal to control the distance between the tip and sample, and the amplitude was kept constant using a lock‐in amplifier and a homemade automatic gain controller. Due to the mechanical stability, the sensor shows a high quality factor (∼103), and the image quality obtained with this sensor was equivalent to that of the cantilever‐based AFM. SCANNING 36:632–639, 2014. © 2014 Wiley Periodicals, Inc.